Cadmium Recovery from Spent Ni-Cd Batteries: A Brief Review - Ervins Blumbergs (MDPI AG, 2021)
The significant increase in the demand for efficient electric energy storage during the past decade has promoted an increase in the production and use of Cd-containing batteries. On the one hand, the amount of toxic Cd-containing used batteries is growing, while on the other hand, Cd is on a list of critical raw materials (for Europe). Both of these factors call for the development of effective technology for Cd recovery from spent batteries. The present paper is aimed at providing a short review of the recent progress in Cd recovery from spent batteries. Statistical data from the past decade on the source of Cd, its global production, and Ni-Cd battery recycling are given in the introduction. A short overview of the pyro-and hydro-metallurgical methods of metal production is provided. Recent progress in Cd recovery by commercial methods during the past decade is reviewed.